Peningkatan Prestasi Belajar IPS melalui Penerapan Model Kooperatif Make a Match Masa Covid-19 pada Siswa Kelas VII- C SMPN 3 Masbagik Tahun Pelajaran 2020/2021 - Mustiani, Mustiani (MASALIQ, 2021)
This research is a class action research (CAR) aimed at improving Social Studies learning achievement which is carried out in class VII-C students of SMPN 3 Masbagik using the Make a Match Learning Model. The researcher conducted an action research with the aim of knowing the improvement of social studies learning achievement in grade VII-C students of SMPN 3 Masbagik through the application of the Make a Match learning model. Based on the results of research and discussion of the Make a Match learning model, it can improve social studies learning activities and achievement for class VII-C students of SMPN 3 Masbagik in the odd semester of the 2020/2021 school year. This increase can be seen from the acquisition of student activity scores and the average class value and the level of classical completeness in each cycle has increased both in cycle I and cycle II. Based on the results of data analysis in each cycle, it appears that the results from cycle I to cycle II have increased. In the implementation of learning and the results of the first cycle of data analysis, for student activities an average value of 3.00 was obtained and student activities in the second cycle obtained an average grade of 4.40 while classical completeness was obtained in the first cycle of 68% and increased in cycle II by 90%